School Career Counselling and Individual Career Planning As Perceived by Secondary School Students - Agnieszka PAWLUK-SKRZYPEK; Monika JUREWICZ (Communications of International Proceedings, 2022)
The subject of the study was the opinions of final-year students of general secondary/high schools on the importance of school career counselling in the process of planning their individual career development. In the context of today's reality, in which we are experiencing numerous changes in the labour market, school education is increasingly in need of informed, purposeful and professional career counselling activities and planning for this development is today a necessity and a lifelong task. The research has shown that, in the perception of students in their final year of general secondary/high school, school career counselling activities are very important and necessary for planning their individual career development. However, the students' evaluation of these activities is not positive. The research carried out indicates that there is a need to raise the awareness of staff in educational institutions, in the area of goals and tasks as regards vocational counselling that are incumbent on them and to strengthen the care for their professionalism. The basis of any activity in this area should be a sound diagnosis of students' expectations and an adequate plan for responding to them.
Keywords: school career counselling; career planning; young people